1998
DOI: 10.1111/j.1439-0507.1998.tb00308.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage by gliotoxin from Aspergillus fumigatus. An occupational and environmental propagule: adduct detection as measured by 32P DNA radiolabelling and two‐dimensional thin‐layer chromatography

Abstract: Gliotoxin is produced by the fungus Aspergillus fumigatus. Aspergillus is widespread in the environment and this ubiquitous nature results in disease and co-carcinogenesis to be distributed world-wide. Gliotoxin contains an epipolythiodioxopiperazine (ETP) ring that is believed to be involved in redox reactions. The reactive oxygen species produced interact with DNA to form hydroxylated and other altered DNA products. To measure DNA adduct formation, we used 32P radiolabelling and, after enzymatic DNA digestio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…In this specific case, the toxins were not associated with spores or mycelium but rather were absorbed into the materials themselves. The concentrations of gliotoxin known to lower ciliary beating frequency or cause DNA adduct formation were above 0.2 and 32.6 g/ml, respectively (1,6). These can be compared to the levels detected in the experimentally mold-damaged building materials reported here, from 1 to 40 ng of gliotoxin per cm 2 depending on the building material tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this specific case, the toxins were not associated with spores or mycelium but rather were absorbed into the materials themselves. The concentrations of gliotoxin known to lower ciliary beating frequency or cause DNA adduct formation were above 0.2 and 32.6 g/ml, respectively (1,6). These can be compared to the levels detected in the experimentally mold-damaged building materials reported here, from 1 to 40 ng of gliotoxin per cm 2 depending on the building material tested.…”
Section: Discussionmentioning
confidence: 99%
“…These reactive oxygen species or other radicals generated through redox cycling are also capable of causing DNA damage as demonstrated elsewhere in in vitro studies (3,5,6). In this study, we found that bacterial DNA repair systems appear to The mechanism of colonization is still poorly understood, but the ability of culture filtrates of A. fumigatus to decrease ciliary beating frequency (gliotoxin has been identified as a cilioinhibitory factor) and to damage human respiratory epithelium in vitro (R. Amitani, A. Sato, Y. Matsui, A. Niimi, K. Yamada, E. Tanaka, T. Murayama, K. Maeda, and F. Kuze, American Thoracic Society meeting, Am.…”
Section: Discussionmentioning
confidence: 99%
“…We developed 32 P-post-labeling 2-D TLC assay to detect radioactivity labeled nucleic acid components quantitatively and qualitatively [20]. This assay has been successfully reported to measure 2 -deoxyuridine-3 -monophosphate (dUMP) adduct [21], 5-bromo-2 -deoxiuridine (BUDR) adduct [22], and gliotoxin induced adduct [23] in tested DNA samples. This technique is sensitive enough to detect one adduct per 10 5 nucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…One can use as much specific chemical characterization as possible (58) but ultimately rely on fingerprint analysis. Many published figures demonstrate examples of fingerprint chromatograms (55,56,59).…”
Section: Analyte Identificationmentioning
confidence: 98%